The Institutional Role in Vocational Training in The Basque Country: Something More Than Just Temporary Support - Murua Cartón, Hilario; Dávila Balsera, Paulí (Historia y Memoria de la Educación, 2023)
The Vocational Training (VT) has been an educational model that during decades has not been evaluated by Spanish state. This lack of interest from the academic authorities was solved during Franco’s dictatorship by different agents (church, unions, companies, …) that contributed to the development. With the passing of Basque Country Autonomy Statute, and the creation of the Basque Government, that accepted the responsibility of the VT, the different agents still maintain their labour. In this article, taking into account the legislation, we are going to analyse how has been the support of the Basque institutions (government, council, local government) form 1979 until nowadays keeping in mind the history of the basque VT